Developing Sasak ethnicity comic character-based student worksheets to improve students’ critical thinking skills - Atika Malahilla; Muhammad Nizaar; Haifaturrahmah Haifaturrahmah; Najamudin Najamudin; Emese K. Nagy (JINoP (Jurnal Inovasi Pembelajaran), 2023)
Critical thinking skill is one of the top-notch thinking abilities required in the 21st century. Training students' critical thinking is not easy for teachers, so it takes an exciting learning media and contextual student worksheet to students' lives. Meanwhile, the available student worksheet from the government and publishers is less attractive and contextual. This study is a research and development of a 4D model with the stages comprising definition, design, development, and dissemination. The study recruited four-grade elementary school students, as many as 26 students. The test instrument was developed based on critical thinking ability indicators. The trial test of the student worksheet employed a group pretest-posttest design. The expert judgment result on the student worksheet prototype analyzed using Aiken V showed a very good category score and feasibility to be tested in the trial. The student worksheet trial test result indicated that Sasak ethnicity comic character-based student worksheets affect students' critical thinking. The students liked very much on the comic design very much, such as the Sasak ethnicity wardrobe design, the conversation location, and the issues discussed in the comic are contextual to real-life events, so the students were enthusiastic and critical in the discussion.